Near Infrared‐Triggered Theranostic Nanoplatform with Controlled Release of HSP90 Inhibitor for Synergistic Mild Photothermal and Enhanced Nanocatalytic Therapy with Hypoxia Relief (Small 28/2022). Issue 28 (14th July 2022) - Tian, Boshi; Wang, Chen; Du, Yaqian; Dong, Shuming; Feng, Lili; Liu, Bin; Liu, Shikai; Ding, He; Gai, Shili; He, Fei; Yang, Piaoping
Abstract : Hypoxic Tumor Therapy In article number 2200786, Lili Feng, He Ding, Piaoping Yang, and co‐workers develop a near‐infrared (NIR)–triggered nanoplatform with controlled release of a heat shock proteins (HSPs) inhibitor for synergistic mild photothermal and enhanced Fenton nanocatalysis. Upon NIR irradiation, gambogic acid is released and inhibits the expression of HSP90. Notably, the nanoplatform simultaneously relieves the tumor hypoxia and enhances the efficacy of the nanocatalytic therapy in an acidic tumor microenvironment.